Моделирование потока в межлопаточном канале компрессора с учетом вращения рабочего колеса для определения аэродинамических сил - Карпик, Анна Александровна (НТУ "ХПИ", 2017)
Представлено численное моделирование турбулентного вязкого течения газа на основе уравнений Навье-Стокса осредненных по Рейнольдсу (RANS–модель). Результаты расчета течения в нестационарной трехмерной постановке получены с помощью программного комплекса F. Численный анализ проводился с целью исследования характера течения в венце рабочих лопаток с учетом взаимодействия между ними. Получено распределение полей давления и скорости в разные моменты времени при вращении рабочего колеса. В межлопаточном канале выявлены неблагоприятные зоны течения.

This paper presents numerical simulation of turbulent viscous flows using the Reynolds averaged Navier-Stokes (RANS) equations. The gas-dynamic simulation is required to estimate the vibration strength and additional losses caused by the periodic non-stationarity of the gas flow. The non-uniformity of the flow represents itself as a non-uniformity of the fields of the velocity and pressure in front of and behind the working blades. The simulation is carried on for a model describing allthe properties, such as compressibility, viscosity, 3D effects, influence of the radial gap, leakages etc. The differential two-parametrical k-ω SST Menter's model is used as a model of turbulence. The values of the flow parameters in the non-stationary three-dimensional formulation are obtained using the F solver. Numerical analysis is used to investigate the character of the flow in the rotor, in particular the blade interaction. The modelallows determining the flow in the blade channel and zones of the adverse flow. The basic factors causing non-uniformity and non-stationary of the gas flow are determined. The pressure and velocity fields at different times during the rotation of the runner are computed.
Simulation of the flow in the compressor blade channel taking into account the rotation of the runner for the estimation of aerodynamic forces
Keywords: численное моделирование; вязкое течение; нестационарность; уравнения Навье-Стокса; RANS-модель; blade channel; numerical simulation; viscous flow; non-stationarity